A Moderate Increase of Physiological CO2 in a Critical Range during Stable NREM Sleep Episode: A Potential Gateway to REM Sleep - Madan, Vibha; Jha, Sushil K. (Frontiers in Neurology, 2012)
Sleep is characterized as rapid eye movement (REM) and non-rapid eye movement (NREM) sleep. Studies suggest that wake-related neurons in the basal forebrain, posterior hypothalamus and brainstem and NREM sleep-related neurons in the anterior-hypothalamic area inhibit each other, thus alternating sleep-wakefulness. Similarly, pontine REM-ON and REM-OFF neurons reciprocally inhibit each other for REM sleep modulation. It has been proposed that inhibition of locus coeruleus (LC) REM-OFF neurons is pre-requisite for REM sleep genesis, but it remains ambiguous how REM-OFF neurons are hyperpolarized at REM sleep onset. The frequency of breathing pattern remains high during wake, slows down during NREM sleep but further escalates during REM sleep. As a result, brain CO2 level increases during NREM sleep, which may alter REM sleep manifestation. It has been reported that hypocapnia decreases REM sleep while hypercapnia increases REM sleep periods. The groups of brainstem chemosensory neurons, including those present in LC, sense the alteration in CO2 level and respond accordingly. For example; one group of LC neurons depolarize while other hyperpolarize during hypercapnia. In another group, hypercapnia initially depolarizes but later hyperpolarizes LC neurons. Besides chemosensory functions, LC’s REM-OFF neurons are an integral part of REM sleep executive machinery. We reason that increased CO2 level during a stable NREM sleep period may hyperpolarize LC neurons including REM-OFF, which may help initiate REM sleep. We propose that REM sleep might act as a sentinel to help maintain normal CO2 level for unperturbed sleep.